Awareness, function, theme, and collaborative governance of public’s perception of Alor Gajah, Malacca art space - Azahar Harun; Sharmiza Abu Hassan; Khairunissa Mohd Abd Ghani; Tengku Intan Suzila Tengku Sharif; Pattanachotti, Ohm (Penerbit Universiti Kebangsaan Malaysia, 2023)
The urban landscapes of Malacca town in Malaysia boast a wide variety of public art pieces that serve to beautify and provide distinctive township identity. Despite the prevalence of public art, the impact on the urban landscape and how it shapes the public’s perception have been scarcely disclosed. This study sought to fill these gaps by examining the public's perception of the existing public art in the town of Alor Gajah, Malacca. This survey study involved 271 respondents. Their perceptions were deductively themed into Awareness, Function, Theme, and Collaborative Governance. The findings accounts that the public is aware of the function and theme of public art in Alor Gajah town, but their perception of collaborative governance is lacking. Respondents perceived the public art installations as urban ornaments that could enhance the visual appeal of the town; however, poor design execution and subpar maintenance were found to contribute to low perceived governance. These findings suggest that public attitude towards existing public art is an important factor in supporting the Alor Gajah Municipal Council in managing and developing quality living conditions. While public art is a popular strategy to enhance the visual appeal and cultural significance of urban landscapes in Malacca, it is important to evaluate the public’s perception of such installations and successes to achieve the intended purpose. These may ensure the public appreciation and thus instill a sense of proprietary, guardianship and honor.